2021
DOI: 10.1186/s12866-021-02336-6
|View full text |Cite
|
Sign up to set email alerts
|

Beware of pharyngeal Fusobacterium nucleatum in COVID-19

Abstract: Background Fusobacterium nucleatum (F. n) is an important opportunistic pathogen causing oral and gastrointestinal disease. Faecalibacterium prausnitzii (F. p) is a next-generation probiotic and could serve as a biomarker of gut eubiosis/dysbiosis to some extent. Alterations in the human oral and gut microbiomes are associated with viral respiratory infection. The aim of this study was to characterise the oral and fecal bacterial biomarker (i.e., F. n and F. p) in COVID-19 patients by qPCR and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 64 publications
1
15
0
Order By: Relevance
“…Previous studies have reported that Prevotella could drive inflammation, dampen innate immune responses [ 27 ], and contribute to oral inflammatory processes [ 28 ]. Abdul et al found that the over-expressed Prevotella proteins could promote viral infection, suggesting that Prevotella plays an important role in in the progression of COVID-19 [ 29 , 30 ]. Taken together, these findings indicated that the increase in butyrate-producing Fusobacterium and the decrease in the opportunistic pathogen Prevotella contribute to the recovery of SARS-CoV-2 infection.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that Prevotella could drive inflammation, dampen innate immune responses [ 27 ], and contribute to oral inflammatory processes [ 28 ]. Abdul et al found that the over-expressed Prevotella proteins could promote viral infection, suggesting that Prevotella plays an important role in in the progression of COVID-19 [ 29 , 30 ]. Taken together, these findings indicated that the increase in butyrate-producing Fusobacterium and the decrease in the opportunistic pathogen Prevotella contribute to the recovery of SARS-CoV-2 infection.…”
Section: Discussionmentioning
confidence: 99%
“…Over the last decade, several studies, albeit focusing primarily on adults, have reported an increasing trend in anaerobic pathogen isolation; however, the leading pathogens remain aerobic in nature 28,29 . We suspect that the Fusobacterium and Streptococcus Anginosus surge apparent in our cultures stemmed from alterations in the normal oral and oropharyngeal flora, a phenomenon previously described during the pandemic 30,31 . We presume that these changes were a byproduct of pandemic‐imposed non‐pharmaceutical interventions, namely mask usage, lockdowns and social distancing.…”
Section: Discussionmentioning
confidence: 79%
“…Colonization of oropharynx or lower respiratory tract led to the risk of ventilator-associated pneumonia [44]. In addition, it was significantly increased in COVID-19 patients [45]. Therefore, increased Fusobacterium nucleatum in oral microbiome may be the pathogen responsible for postoperative pneumonia at both initial visit and after preoperative oral care management.…”
Section: Discussionmentioning
confidence: 99%